Zagreb Indices of Some New Graphs - Alameri, Abdu; Ali, Esmail; Modabish, A. (Science Academic Scholars Association (SASA), 2018)
In this paper, we introduce Zagreb Indices of Some New Graphs. Exactly, first index, second index and forgotten index. New graphs are generated from the initial graphs by graph operations. We also created some possible applications on the Zagreb indices as special cases